2016
DOI: 10.1186/s12885-016-2206-4
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid tagged nanoceria as a novel therapeutic agent in ovarian cancer

Abstract: BackgroundNanomedicine is a very promising field and nanomedical drugs have recently been used as therapeutic agents against cancer. In a previous study, we showed that Nanoceria (NCe), nanoparticles of cerium oxide, significantly inhibited production of reactive oxygen species, cell migration and invasion of ovarian cancer cells in vitro, without affecting cell proliferation and significantly reduced tumor growth in an ovarian cancer xenograft nude model. Increased expression of folate receptor-α, an isoform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 51 publications
2
73
2
Order By: Relevance
“…Because the cytotoxicity of PTX/Fol‐c 1 ‐β‐CyD was decreased by knockdown of PCFT, but not FRα, in A2780 cells, it is likely that PTX/Fol‐c 1 ‐β‐CyD uptake in A2780 cells is mediated primarily through PCFT (Figure 3C). Aside from in this study, A2780 and SK‐OV‐3 cells are frequently used as target cells in studies of FRα‐targeting drugs for ovarian cancer 16,36‐40. Some studies have compared expression levels of FRα between A2780 and SK‐OV‐3 cells, and in all of the studies, consistent with our results, A2780 cells expressed lower levels of FRα than SK‐OV‐3 cells 16,37,39.…”
Section: Discussionsupporting
confidence: 87%
“…Because the cytotoxicity of PTX/Fol‐c 1 ‐β‐CyD was decreased by knockdown of PCFT, but not FRα, in A2780 cells, it is likely that PTX/Fol‐c 1 ‐β‐CyD uptake in A2780 cells is mediated primarily through PCFT (Figure 3C). Aside from in this study, A2780 and SK‐OV‐3 cells are frequently used as target cells in studies of FRα‐targeting drugs for ovarian cancer 16,36‐40. Some studies have compared expression levels of FRα between A2780 and SK‐OV‐3 cells, and in all of the studies, consistent with our results, A2780 cells expressed lower levels of FRα than SK‐OV‐3 cells 16,37,39.…”
Section: Discussionsupporting
confidence: 87%
“…They also found that angiogenesis in the tumors was reduced in treated mice as indicated by less CD31-positive staining. The same group also reported that surface functionalization of CeO 2 nanoparticle with folic acid and its co-delivery with cisplatin further decreased the tumor burden and angiogenesis [157]. In other studies, CeO 2 nanoparticle administration to carbon-tetrachloride (CCl 4 )-induced liver fibrosis mice was shown to inhibit oxidative [158], [159] and endoplasmic reticulum stress signaling pathways as well as reduction in inflammatory cytokines such as TNF-α and IL-1β [158].…”
Section: Strategies To Suppress Oxidative Stressmentioning
confidence: 88%
“…Nanoparticle coating or stabilization is typically utilized to achieve reduced reticuloendothelial uptake (Murugan et al, 2015), direct the nanoparticle to a particular tissue target (Cimini et al, 2012;Hijaz et al, 2016), or to provide a functional property such as reduced angiogenesis (Lord et al, 2013). Minor changes to surface chemistry, for example by varying the density of polyethylene glycol coating, yield distinct profiles of corona proteins and differing macrophage uptake patterns (Walkey et al, 2012).…”
Section: Discussionmentioning
confidence: 99%